The consequences of (not) seeing eye-to-eye about the past: The role of supervisor–team fit in past temporal focus for supervisors' leadership behavior - Roman Briker; Frank Walter; Michael S. Cole (Journal of Organizational Behavior, 2019)
This study seeks to advance our understanding of the leadership consequences that may ensue when supervisors and their teams have similar versus differing orientations toward the past. Integrating a leader–team fit perspective with functional leadership theory, we cast incongruence between supervisor and team past temporal focus as a key antecedent of supervisors' active (i.e., task-oriented and relationship-oriented) and passive (i.e., laissez-faire) leadership behaviors toward the team. We tested our hypotheses in a team-level study that included a field sample of 84 supervisors and their teams using polynomial regression and response surface analyses. Results illustrated that supervisors demonstrated more task-oriented and relationship-oriented leadership when supervisors' and their team's past temporal focus were incongruent rather than aligned. Furthermore, in situations of supervisor–team congruence, supervisors engaged in less task-oriented and relationship-oriented leadership and more laissez-faire leadership with higher (rather than lower) levels of supervisor and team past temporal focus. In sum, these findings support a complex (mis)fit model such that supervisors' attention to the past may hinder their productive leadership behaviors in some team contexts but not in others. Hence, this research advances a novel, multiple-stakeholder perspective on the role of both supervisors' and their team's past temporal focus for important leadership behaviors.
Keywords: 650; laissez-faire leadership; past temporal focus; relationship-oriented leadership; task-oriented leadership; time perspective